Utilizing mesenteric near‐infrared reflectance spectroscopy to predict gastrointestinal complication risks and optimize feeding strategies in infants undergoing cardiac surgery - Wenpeng Xie; Yinan Liu; Yating Zeng; Yirong Zheng; Qiang Chen (Pediatric Investigation, 2024)
ABSTRACT Importance Gastrointestinal complications are common perioperative complications in children with congenital heart disease (CHD), and as near‐infrared reflectance spectroscopy (NIRS) provides a non‐invasive, real‐time monitoring of regional tissue oxygenation, we envisioned monitoring and preventing the development of gastrointestinal complications through the use of NIRS. Objective To assess the utility of NIRS for predicting gastrointestinal complication risks and determining optimal initial feeding times in infants post‐cardiac surgery. Methods This retrospective study included 65 infants with CHD treated at our hospital from January 2021 to January 2022. We collected and analyzed data on mesenteric regional venous and arterial oxygen saturation, arterial partial pressure of oxygen, first lactic acid levels, timing of initial enteral feeding, and incidence of gastrointestinal complications. Results Out of 65, 61 infants were eligible for inclusion (four cases were excluded). Infants with gastrointestinal complications post‐surgery showed significantly lower mesenteric NIRS values and earlier feeding times compared to those without complications (55.5 ± 3.3 vs. 59.6 ± 6.3, P = 0.029; and 59.8 ± 6.7 vs. 66.9 ± 5.7, P = 0.002, respectively). Multivariable binary logistic regression analysis revealed that mesenteric NIRS readings at the time of initial feeding independently predicted gastrointestinal complications (odds ratio, 0.802; 95% confidence interval, 0.693–0.928; P = 0.003). receiver operating characteristic curve analysis indicated a significant predictive value of mesenteric NIRS at initial feeding time (area under the curve: 0.799), with a suggested critical threshold of 63.1% (93% sensitivity, 70% specificity). Pearson correlation test confirmed a significant association between mesenteric NIRS at initial feeding time and the establishment of enteral feeding. Interpretation Mesenteric NIRS measurements at the time of initial feeding provide a reliable method for identifying infants at risk of gastrointestinal complications following cardiac surgery and can inform decisions regarding the timing of initial postoperative feeding.